2010
DOI: 10.3109/02770901003801964
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stress in Early Life on Immune Functions in Rats With Asthma and the Effects of Music Therapy

Abstract: Stress in childhood and adulthood resulted in different HPA axis responsiveness in the exacerbation of markers of asthma. These data provide the first evidence of the long-term normalizing effects of music on asthmatic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 36 publications
(46 reference statements)
1
14
0
1
Order By: Relevance
“…Furthermore, specific type of auditory enrichment used here also affected the immune genes expression in zebrafish vs. unexposed controls ( Fig. 3A ), similar to music effects reported earlier in rodents ( Lu et al, 2010 ; Uchiyama et al, 2012 ). Here, fish exposed to auditory enrichment showed lower expression of some pro-inflammatory genes (IL-1β and IFN-γ), but without affecting anti-inflammatory genes IL-10 and IL-4 ( Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, specific type of auditory enrichment used here also affected the immune genes expression in zebrafish vs. unexposed controls ( Fig. 3A ), similar to music effects reported earlier in rodents ( Lu et al, 2010 ; Uchiyama et al, 2012 ). Here, fish exposed to auditory enrichment showed lower expression of some pro-inflammatory genes (IL-1β and IFN-γ), but without affecting anti-inflammatory genes IL-10 and IL-4 ( Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Cross-sectional measurements of HPA and immune function in adulthood may thus vary greatly as a function of relative age of an organism when stressed and/or the chronicity of exposure to a remote stressful environment. The relevance of timing and chronicity effects was illustrated by recent preclinical data demonstrating stress exposure in young rats resulted in the opposite direction changes in both central IL1-β and peripheral corticosterone concentrations than were observed when stress exposure was introduced in adulthood (Lu et al , 2010). …”
Section: Discussionmentioning
confidence: 99%
“…This mediator is low-level maternal corticosterone [95•]. In adult mice and rats, OVA sensitization and challenge increases stress [96101] and increases endogenous serum corticosterone [102, 103]. Moreover, it is reported that symptoms of stress/anxiety are commonly associated with allergy/asthma in adult mice and in humans [104108].…”
Section: Transplacental Mediators and Development Of Allergic Diseasementioning
confidence: 99%